NMR visibility of deuterium‐labeled liver glycogen in vivo - De Feyter, Henk M.; Thomas, Monique A.; Behar, Kevin L.; Graaf, Robin A. (Magnetic resonance in medicine, 2021)
Purpose Deuterium metabolic imaging (DMI) combined with [6,6’‐2H2]‐glucose has the potential to detect glycogen synthesis in the liver. However, the similar chemical shifts of [6,6’‐2H2]‐glucose and [6,6’‐2H2]‐glycogen in the 2H NMR spectrum make unambiguous detection and separation difficult in vivo, in contrast to comparable approaches using 13C MRS. Here the NMR visibility of 2H‐labeled glycogen is investigated to better understand its potential contribution to the observed signal in liver following administration of [6,6’‐2H2]‐glucose. Methods Mice were provided drinking water containing 2H‐labeled glucose. High‐resolution NMR analyses was performed of isolated liver glycogen in solution, before and after the addition of the glucose‐releasing enzyme amyloglucosidase. Results 2H‐labeled glycogen was barely detectable in solution using 2H NMR because of the very short T2 (<2 ms) of 2H‐labeled glycogen, giving a spectral line width that is more than five times as broad as that of 13C‐labeled glycogen (T2 = ~10 ms). Conclusion 2H‐labeled glycogen is not detectable with 2H MRS(I) under in vivo conditions, leaving 13C MRS as the preferred technique for in vivo detection of glycogen.